Classification of glycosidases that hydrolyze the specific positions and types of sugar moieties in ginsenosides. (1st November 2016) - Shin, Kyung-Chul; Oh, Deok-Kun
Abstract: Ginsenosides are the main compounds with pharmacological activities in ginseng. Deglycosylated ginsenosides, which are more pharmacologically active than glycosylated ginsenosides, can be produced by the specific or nonspecific hydrolysis of the sugar moieties in glycosylated ginsenosides using glycosidases. The enzymes that hydrolyze specifically ginsenosides with different types can be classified according to the enzymatic activity on the positions, inner and outer residues and types of sugar moieties in ginsenosides. Glycosylated ginsenosides are also hydrolyzed to deglycosylated ginsenosides with different hydrolytic pathways by cell conversion or fermentation. The biochemical properties of glycosidases involved in ginsenoside hydrolysis – ginsenosidases – were newly arranged and reviewed in accordance with different types. The combination of different-type ginsenosidases is suggested herein as an efficient tool to produce industrially important ginsenosides.